39.6k views
0 votes
2. If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation

6x - y - 1
4x - 3y = -11
04-6x + 1) - 3y = -11
04(6x + 1) - 3y = -11
4x - 3(6x - 1) = -11
4x - 3(-6x - 1) = -11

User Jorenar
by
5.9k points

1 Answer

1 vote

Answer:

4x - 3(6x - 1) = -11

Explanation:

Solving the first equation for y, we get ...

6x -y = 1 . . . . . given

6x -1 = y . . . . . add y-1 to both sides

Then, filling in for y, we have ...

4x -3y = -11 . . . given

4x -3(6x -1) = -11 . . . . using 6x-1 in place of y . . . matches 3rd choice

User Patrick Ziegler
by
5.5k points